Aktivitas Antiplasmodium Daun Sernai (Wedelia Biflora) Berdasarkan Evaluasi Fungsi Ginjal dan Hati pada Mencit yang Diinfeksi dengan Plasmodium berghei - ., Isa; ., Rinidar; ., Sugito (Jurnal Veteriner, 2013)
This study aimed to determine the antiplasmodial activity of sernai leaves (Wedelia biflora) extractagainst Plasmodium berghei which were infected to mice experimentally using the 4-days suppressive testmethod. The extraction was performed by maceration in three different solvents: ethanol, n-hexane, andethyl acetate. Inoculation of 1x106 P. berghei was performed in 60 Swiss mice intraperitoneally. Theantiplasmodial activity of the ethanol, n-hexana, and ethyl-acetate leaves extract at 4 different doses(100, 80, 60 and 40 mg/kg BW/day, respectively) were tested against P. berghei in vivo for 4 consecutivedays. Animals were given the leaves extracted orally. The negative-control animals were given dimethylsulfoxide diluents (DMSO) and animals in the positive-control were treated with P.berghei + DMSO.Parasitemia status were observed from day 1-4 by thin blood smear from tail and stained with Giemsa.On day 5, levels of urea, creatinine, SGPT and SGOT were measured. The results showed that extract ofsernai leaves using ethanol, n-hexane, and ethyl acetate had the antiplasmodial capacity on P.berghei inmice with effective doses (ED50) of 5.379 mg/kg BW, 25.306 mg/kg BW, and 27.442 mg/kg BW, respectively.The sernai leaves extract had the capability to maintain the liver function but not the kidney function.
Keywords: Plasmodium berghei, Wedelia biflora, malaria, antiplasmodial